A study of the fatigue behaviour of microconcrete model beams under moving load - Macam, Victor R.
Single-reinforced microconcrete beams without web reinforcement were tested under a static load, a fixed-point repeated load and a moving load. The beams have constant cross sections - 5-cm. wide and 8-cm. high and varied span lengths of 40 cm., 60 cm., 80-cm., and 100 cm. The results of the tests in microconcrete beams subjected to static load and fixed-point repeated load were found to be comparable with the results on normal concrete beams as reported in the literature. The fatigue characteristic of microconcrete beams subjected to fixed-point repeated load is similar to that of normal concrete beams. Microconcrete beams under a moving load, irrespective of span lengths, failed in shear. Furthermore, the fatigue strength of microconcrete beams under a moving load was found to be much lower than that of the beams subjected to a fixed-point repeated load. This behavior is attributed to the fact that under moving load, the beam is subjected to a higher shear stress range than that of the fixed-point repeated load. Aside from this, as the load traverse the beam, all the points on the beam are subjected to a combination of high shear and high moment resulting in a complicated crack pattern and consequently, structural disintegration.